2017
DOI: 10.1016/j.omtm.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Lentivector Iterations and Pre-Clinical Scale-Up/Toxicity Testing: Targeting Mobilized CD34 + Cells for Correction of Fabry Disease

Abstract: Fabry disease is a rare lysosomal storage disorder (LSD). We designed multiple recombinant lentivirus vectors (LVs) and tested their ability to engineer expression of human α-galactosidase A (α-gal A) in transduced Fabry patient CD34+ hematopoietic cells. We further investigated the safety and efficacy of a clinically directed vector, LV/AGA, in both ex vivo cell culture studies and animal models. Fabry mice transplanted with LV/AGA-transduced hematopoietic cells demonstrated α-gal A activity increases and lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…The ASAH1 (experimental lentivirus) and α-galactosidase A (AGA, control lentivirus) vectors were provided by J.A.M. Generation of the transfer plasmid, pDY-AGA, was described previously (26). pDY-ASAH1 was constructed using similar methods.…”
Section: Resultsmentioning
confidence: 99%
“…The ASAH1 (experimental lentivirus) and α-galactosidase A (AGA, control lentivirus) vectors were provided by J.A.M. Generation of the transfer plasmid, pDY-AGA, was described previously (26). pDY-ASAH1 was constructed using similar methods.…”
Section: Resultsmentioning
confidence: 99%
“…84 Research is also under way for a gene therapy approach to achieve tissue-specific overexpression of GLA, resulting in a clinical trial (https://clinicaltrials.gov/ ct2/show/NCT02800070?term5gene1therapy&cond5fabry& rank53). 85…”
Section: Oral Therapymentioning
confidence: 99%
“…ACDase deficiency is an attractive target for gene therapy because it is caused by a single gene defect. In fact, several gene therapies for monogenic lysosomal storage disorders are currently being investigated in clinical trials [ 170 172 ]. In the context of ACDase deficiency, one early study demonstrated that FD patient cells recovered ACDase activity when the cells were infected with an onco-retroviral vector that engineered expression of human ACDase [ 173 ].…”
Section: Research Treatment and Future Therapymentioning
confidence: 99%